On the Reliability of the Notion of Native Signer and Its Risks - Zorzi, Giorgia; Giustolisi, Beatrice; Aristodemo, Valentina; Cecchetto, Carlo; Hauser, Charlotte; Quer, Josep; Sánchez Amat, Jordina; Donati, Caterina (Frontiers in Psychology, 2022)
Who is a native signer? Since around 95% of deaf infants are born into a hearing family, deaf signers are exposed to a sign language at various moments of their life, and not only from birth. Moreover, the linguistic input they are exposed to is not always a fully-fledged natural sign language. In this situation, is the notion of native signer as someone exposed to language from birth of any use? We review the results of the first large-scale cross-linguistic investigation on the effects of age of exposure to sign language. This research involved about 45 Deaf adult signers in each of three sign languages (Catalan Sign Language, French Sign Language and Italian Sign Language). Across the three languages, partic-ipants were divided into three groups – those exposed from birth, those between 1 and 5 years of age, and those exposed between 6 to 15 years of age – and received a battery of tests designed for each language targeting various aspects of morphosyntactic competence. In particular, the tests focused on both those morphosyntactic phenomena that are known from the spoken language literature to be good detectors of language impairment or delay (i.e., wh- interrogatives and relative clauses) and on mor-phosyntactic phenomena that are sign language specific (i.e., role shift and directional verbs). The results showed a clear effect of being native, with significant differences across language and tests between signers exposed to sign language from birth and those exposed in the first years of life. This confirms the life-long importance of language exposure from birth and the reliability of the notion of ‘nativeness’, at least for syntax. On the other hand, while in most domains the differences observed between populations might be differences in performance, for some specific constructions, signers be-longing to the three groups may have different grammars. This latter finding challenges the generalized use of native signer’s grammar as the baseline for language description and language assessment.